Handbook of inorganic substances 2013 - Villars, P. (Handbook of inorganic substances ;, 2013)
Since the discovery of X-ray diffraction in 1913 over 100 000 different inorganic substances (also called compounds or phases) have been structurally characterized. The aim of this reference work is to provide the researcher with a comprehensive compilation of all up to now crystallographically identified inorganic substances in only one volume. All data have been processed and critically evaluated by the ""Pauling File"" editorial team using a unique software package. Each substance is represented in a single row containing information adapted to the number of chemical elements.